INTERAKSI BAP DAN NAA TERHADAP PERTUMBUHAN EKSPLAN ANGGREK VANDA SECARA IN-VITRO - Selvia Sutriana; Hasan Basri Jumin; Mardaleni Mardaleni (DINAMIKA PERTANIAN, 2014)
This research aims to obtain the combination of BAP and NAA concentration which give the best effect on explant growth of Vanda orchid in-vitro. The research was conducted at the biotechnology laboratory Faculty of Agriculture Riau Islamic University Pekanbaru from August to December 2013. The completely randomized design with two factorials (BAP and NAA) was used. The observed parameters included percentage of shoot growing, shoot age, shoot height, shoot number and abnormal embryo somatic. Data were analysed using statistics and BNJ Test at the 5% significance level. The result showed that,interactionally,BAP and NAA applications had a significant effect on height plant with the best concentration without BAP and 1.0 ppm NAA. Individually, the application of BAP effected significantly on percentage of shoot growing, shoot growth, shoot height and shoot number with the best concentration without BAP and 0.1 BAP. Furthermore, the application of NAA influenced significantly on percentage of shoot growing, shoot age, shoot height and shoot number with the best concentration of 1.0 ppm NNA